Dermot A. Lane: Stepping Stones to Other Religions. A Christian Theology of Inter-Religious Dialogue.Maryknoll, New York: Orbis Books, 2011. 328 p. ISBN 978-1-57057-991-8 (pbk.) - Peelman, Achiel (Annales Missiologici Posnanienses, 2015)
Recenzja